337 Symptom Severity After High-School Football-Related Concussion Varies by Time Point In A Season: An Initial Investigation. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Brett, Benjamin L; Kuhn, Andrew W; Yengo-Kahn, Aaron M; Kerr, Zachary Y; Bonfield, Christopher M; Solomon, Gary; Zuckerman, Scott L
Abstract: INTRODUCTION: Several sport-related factors have been shown to be associated with symptom reporting patterns after sport-related concussion (SRC). The current objective was to determine if acute symptom presentation following SRC differed by time point within a high school football season. METHODS: A multicenter, ambispective cohort of high-school football players who sustained a SRC (n = 2594) was conducted. Timing (early, mid, and late season) of SRC was based on median dates for the start of the pre-season, regular season, and playoffs of each state's football schedule. Analysis of covariance (ANCOVA) investigated differences across season period groups for (1) total symptom scores (TSS), and (2) individual symptom increases from baseline within 1-wk postinjury. RESULTS: Significant group differences were observed in TSS (F = 15.40, P < .001) and individual symptom increases from baseline (F = 16.40, P < .001). Significant increases were seen from baseline to both mid-season and late season in both TSS (F = 0.10, P < .001) and individual symptoms (F = 0.10, P = .006). Post hoc tests indicated a linear trend, with late-season injured athletes reporting approximately twice the TSS (13.10 vs 6.77) and new symptoms (5.70 vs 2.68) as those with early-season injuries. Overall, both outcomes of symptom severity and symptom increase from baseline appeared to increase as the football season continued. CONCLUSION: In a cohort of American high school football student athletes, those suffering SRC in the late-season time period had increased acute symptom burden compared to early-season SRC. SRC sustained later in-season may require more conservative management.